Dietary antioxidants and exercise - Powers, S. K.; DeRuisseau, K. C.; Quindry, J.; Hamilton, K. L. (Journal of Sports Sciences, 2004)
Muscular exercise promotes the production of radicals and other reactive oxygen species in the working muscle. Growing evidence indicates that reactive oxygen species are responsible for exercise-induced protein oxidation and contribute to muscle fatigue. To protect against exercise-induced oxidative injury, muscle cells contain complex endogenous cellular defence mechanisms (enzymatic and non-enzymatic antioxidants) to eliminate reactive oxygen species. Furthermore, exogenous dietary antioxidants interact with endogenous antioxidants to form a cooperative network of cellular antioxidants. Knowledge that exercise-induced oxidant formation can contribute to muscle fatigue has resulted in numerous investigations examining the effects of antioxidant supplementation on human exercise performance. To date, there is limited evidence that dietary supplementation with antioxidants will improve human performance. Furthermore, it is currently unclear whether regular vigorous exercise increases the need for dietary intake of antioxidants. Clearly, additional research that analyses the antioxidant requirements of individual athletes is needed.